Measuring misconceptions about traumatic brain injury: are existing scales misconceived?. (28th July 2020) - Bryant, Eleanor; Williams, Claire; Horry, Ruth; Worthington, Andrew
ABSTRACT: Primary Objectives: The aim of this paper was to conduct a review of the misconception literature relating to traumatic brain injury (TBI) and to critically review the comprehensiveness, psychometric properties and other qualities of existing scales designed to measure knowledge and misconceptions of TBI. Methods: Terms relating to misconceptions, misconception scales, public perceptions and traumatic brain injury were used to identify existing scales. The initial search was expanded using the reference lists and citations of relevant articles. Main Outcomes: Eight scales were identified for full review, with several sharing a common set of items. The majority of scales were designed to measure public perceptions of TBI, although some were developed for use in specific populations (e.g. sports, professional samples). Existing scales are limited by their scope and breadth of coverage, adoption of a medicalized view of TBI, scaling and scoring issues, failure to use a conceptual framework, and by numerous psychometric issues related to reliability and validity. Conclusions: There are a number of weaknesses attached to existing scales. Several recommendations are made to promote and inform future scale development.